Application of a high‐resolution in vitro human MDR1‐MDCK assay and in vivo studies in preclinical species to improve prediction of CNS drug penetration - Licong Jiang; Sanjeev Kumar; Marc Nuechterlein; Marissa Reyes; Dao Tran; Clifford Cabebe; Peggy Chiang; James Reynolds; Scott Carrier; Yongkai Sun; Peter Eddershaw; Tanya Hay; et al. (Wiley, 2022)
Abstract P‐glycoprotein (P‐gp, MDR1) is expressed at the blood-brain barrier (BBB) and restricts penetration of its substrates into the central nervous system (CNS). In vitro MDR1 assays are frequently used to predict the in vivo relevance of MDR1‐mediated efflux at the BBB. It has been well established that drug candidates with high MDR1 efflux ratios (ERs) display poor CNS penetration. Following a comparison of MDR1 transporter function between the MDR1‐MDCKI cell line from National Institutes of Health (NIH) and our internal MDR1‐MDCKII cell line, the former was found to provide better predictions of in vivo brain penetration than our in‐house MDR1‐MDCKII cell line. In particular, the NIH MDR1 assay has an improved sensitivity to differentiate the compounds with ERs of <3 in our internal cell line and is able to reduce the risk of false negatives. A better correlation between NIH MDR1 ERs and brain penetration in rat and non‐human primate (NHP) was demonstrated. Additionally, a comparison of brain penetration time course of MDR1 substrates and an MDR1 non‐substrate in NHP demonstrated that MDR1 interaction can delay the time to equilibrium of drug concentration in the brain with plasma. It is recommended to select highly permeable compounds without MDR1 interaction for rapid brain penetration to produce the maximal pharmacological effect in the CNS with a quicker onset.